Malignant inflammatory fibrous histiocytoma of bone and acute lymphoblastic leukaemia. Issue 717 (July 1985) - Woodcock, B. E.; Parsons, M. A.; Winfield, D. A.
Abstract : A patient is described who developed a malignant inflammatory fibrous histiocytoma of vertebral bone (MFH) 4 months after the onset of acute lymphoblastic leukaemia. This is the first report of the simultaneous occurrence of these two conditions. Similarities to the more frequent occurrence of another histiocytic malignancy, histiocytic medullary reticulosis, following acute lymphoblastic leukaemia, are noted. The usefulness of gallium scanning to monitor the response of this tumour to treatment is demonstrated.